Expression of fibroblast growth factor 10 and its receptor, fibroblast growth factor receptor 2B, in the bovine corpus luteum - Castilho, A. C. [UNESP]; Giometti, I. C. [UNESP]; Berisha, B.; Schams, D.; Price, C. A.; Amorim, Renée Laufer [UNESP]; Papa, P. C.; Buratini, J. [UNESP] (Wiley-liss, 2008)
There is evidence that several fibroblast growth factors (FGFs) are involved in growth and development of the corpus luteum (CL), but many FGFs have not been investigated in this tissue, including FGF10. The objective of this study was to determine if FGF10 and its receptor (FGFR2B) are expressed in the CL. Bovine CL were collected from an abattoir and classed as corpus hemorrhagica (stage 1), developing (stage 11), developed (stage 111), and regressed (stage IV) CL. Expression of FGF10 and FGFR2B mRNA was measured by reverse transcription-polymerase chain reaction (RT-PCR). Both genes were expressed in bovine CL, and FGF10 expression did not differ between stages of CL development. FGF10 protein was localized to large and small luteal cells by immunohistochemistry. FGFR2B expression was approximately threefold higher in regressed compared to developing and developed CL (P < 0.05). To determine if FGF10 and FGFR2B expression is regulated during functional luteolysis, cattle were injected with PGF2 alpha and CL collected at 0, 0.5, 2, 4, 12, 24, 48, and 64 hr thereafter (n = 5 CL/time point), and mRNA abundance was measured by real-time RT-PCR. FGF10 mRNA expression did not change during functional luteolysis, whereas FGFR2B mRNA abundance decreased significantly at 2, 4, and 12 hr after PGF2a, and returned to pretreatment levels for the period 24-64 hr post-PGF2 alpha. These data suggest a potential role for FGFR2B signaling during structural luteolysis in bovine CL.
Keywords: fibroblast growth factor; corpus luteum; luteolysis; cattle